A BRIEF UNDERSTANDING OF ORGANIZATIONAL AMBIDEXTERITY AND DYNAMIC MANAGERIAL CAPABILITIES, AND HOW THEY RELATE? - Ande, Diin Fitri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
The concept of organizational ambidexterity and dynamic managerial capabilities have raised researchers’ interest. Based on previous studies, this paper aims to provide a simple understanding of those two concepts, so that everyone from diverse backgrounds can easily capture the ideas of these concepts. In addition, the clear explanation of the relationship between dynamic managerial capabilities and organizational ambidexterity also provided. In short, Ambidexterity is defined as the need for the firm to achieve a balance between explore and exploit (He and Wong, 2004; O’Reilly, 2013) and the responsibility to manage both lays on the TMTs. On the other hand, Dynamic managerial capabilities emphasize the important role of managers or leaders to sense, to seize, and to reconfigure organizational skills and resources to match with changing the environment (Eisenhardt and Martin, 2000; Teece et al., 1997). TMTs dynamic managerial capabilities influence their ability to sense opportunities for ambidexterity and seize them through combining, integrating and reconfiguring exploitative and explorative resources and capabilities. Several studies have provided several examples of these two concepts are related. For instance, TMTs’ human capital describe the knowledge, education, experience, and skills of the TMTs, then logically, the TMTs that have rich working experience will be able to manage the resources for exploitative and explorative activities in the better system (Heavey, 2010).